Der Jahresgang der Trockengrenze in Afrika - Lauer, Wilhelm; Frankenberg, Peter (ERDKUNDE, 1979)
Geographical analysis concerning 'arid land boundaries' began in 1910 with the studies of A. Penck. The seasonal variation of arid or humid conditions in Africa had been elaborated since then by means of different methods (fig.1-3), taking absolute or relative precipitation figures as indices of aridity or taking more complex aridity formulae. The following concept of drawing monthly 'arid land boundaries' is based on the calculation of monthly waterbalances (P-E).Three concepts of 'arid land boundaries' are discussed (cf. W.Lauer, P. Frankenberg, 1978).The definition of a 'climatic-ecological arid land boundaries' is based on the concept of 'potential evapotranspiration' (ETP) according to C.W. Thornthwaite (1948). Potential evapotranspiration is calculated as to the formula of J. Papadakis (1966). A month is regarded as humid if precipitation equals or exceeds evapotranspiration (ETP), it is regarded as arid if precipitation is below 'potential evapotranspiration'. Thus 'arid land boundaries' are drawn for each different month. They are all shown together in one map (map 1), thus integrating 12 'arid land boundaries'. The map shows how many months and which period of the year can be defined as humid in Africa. The annual variation of monthly 'arid land boundaries' shows quite strong correlations with the shifting of inter-tropical 'convergence zones' (fig. 5) and 'subtropical high pressure cells'. The main changes in the overall pattern of monthly 'arid land boundaries' take place during may/june and oct./nov. when the 'subtropical high pressure cells' shift abruptly to the north or to the south.